HUBUNGAN BEBAN KERJA PERAWAT INTENSIVE CARE UNIT (ICU) DENGAN TINGKAT STRES PERAWAT - Al Hasan, Moh Shohib (STIKES Widyagama Husada, 2025)
The importance of hospitals understanding nurses' workloads is a key factor in maintaining the quality of healthcare services. This not only affects the well-being of nurses but also has the potential to impact the overall quality of the hospital. This study aims to determine the relationship between nurses' workloads and their stress levels in the ICU at RSUD Dr. Saiful Anwar, East Java Province. The research design used was an observational analytic description with a cross-sectional method. The population involved all nurses in the ICU at RSUD Dr. Saiful Anwar, totaling 85 respondents, with a sample of 70 respondents selected using purposive sampling. The statistical test used was the Spearman Rho test. The statistical test results show that ICU nurses at RSUD Dr. Saiful Anwar have a moderate workload, with 48 respondents (68.6%) falling into this category. Additionally, the level of job stress is also mostly moderate, with 46 respondents (65.7%) in this category. The statistical test results indicated a significant relationship between the nurses' workloads and their stress levels in the ICU, with a correlation coefficient of (+0.296). That workload has a weak influence on work stress. This positive value indicates that the higher the workload the higher the work stress felt by nurses.From these findings, it can be concluded that workload plays a significant role in affecting nurses' stress levels in the ICU. Therefore, hospital management should consider strategies to manage workloads to reduce nurses' stress and improve the quality of healthcare services.